ChemInform Abstract: A Novel and Selective Synthetic Approach for the Access of Pyrrolo[1, 2‐a]imidazol‐7‐one or pyrrol‐3‐one. Issue 51 (5th December 2016) - Zeng, Hui; Yuan, Pengtao; Wang, Fukai; Xu, Xiaoyong; Shao, Xusheng; Li, Zhong
Abstract: Starting from diverse dihydropyrroloimidazol‐6‐ones a mild, metal‐free and operationally simple transformation is developed which offers a solvent‐dependent access to pyrrolo[1, 2‐a]imidazol‐7‐ones (in H2 O) or pyrrol‐3‐ones (in alcohols).